Timescales : thinking across ecological temporalities - Wiggin, Bethany, 1972-; Fornoff, Carolyn; Kim, Patricia Eunji (University of Minnesota Press, 2020)
"Humanists, scientists, and artists collaborate to address the disjunctive temporalities of ecological crisis"--